1999
DOI: 10.1139/v98-210
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the reduction of CrVI to CrIII by D-ribose and 2-deoxy-D-ribose

Abstract: The oxidation of D-ribose and 2-deoxy-D-ribose by CrVI yields the aldonic acid and Cr3+ as final products when an excess of sugar over CrVI is used. The redox reaction occurs through CrVI–>CrIII and CrVI–>CrV–>CrIII paths. The complete rate laws for the CrVI oxidation reactions are expressed by -d[CrVI]/dt = kH[H+]2 [ribose][CrVI], where kH = (5.9 ± 0.1) × 10-2 mol-3 dm9 s-1, and -d[CrVI]/dt = (k0 + kH'[H+]2) [2-deoxyribose][CrVI], where k0 = (1.3 ± 0.5) × 10-3 mol-1 dm3 s-1 and kH' = (4.2 ± 0.1) × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…2a, Set B). These results indicate that under the kinetic experimental conditions, L-sorbose or its oxidation product(s) does not complex with chromium(III) because the spectrum of the reaction mixture remains identical to that of authentic chromium(III) solution ( max = 410 and 570 nm) [18]. The agreement shows that the aquachromium(III) is the final reaction product under any of the conditions used herein.…”
Section: Stoichiometry and Identification Of Reactionsupporting
confidence: 58%
“…2a, Set B). These results indicate that under the kinetic experimental conditions, L-sorbose or its oxidation product(s) does not complex with chromium(III) because the spectrum of the reaction mixture remains identical to that of authentic chromium(III) solution ( max = 410 and 570 nm) [18]. The agreement shows that the aquachromium(III) is the final reaction product under any of the conditions used herein.…”
Section: Stoichiometry and Identification Of Reactionsupporting
confidence: 58%
“…[2]). This is based on the mechanism reported for aldoses, which are also selectively oxidized by Cr VI at the hemiacetalic group with an initial two-electron transfer slow step (21)(22)(23)(24)(25)(26)(27)(28). After the slow redox step, Cr IV is predicted to react with excess saccharide to yield Cr III and a disaccharide radical in a fast step (eq.…”
Section: Discussionmentioning
confidence: 92%
“…Our studies on the reduction of Cr VI and the intermediate Cr V by aldoses (21)(22)(23)(24)(25)(26), deoxyaldoses (27)(28), sugar acids (31,32,35), and methyl glycosides (29)(30) showed that the relative redox reactivities of these saccharides toward chromate are based on the relative rates of the oxidation vs. complexation processes. In view of some preliminary results obtained on the milk-Cr VI system suggesting the formation of long lived lactose-Cr V species generated by direct reaction of Cr VI with lactose (5), we decided to evaluate the kinetics of the reaction of Cr VI with four disaccharides: D-lactose (Lac), D-maltose (Mal), D-cellobiose (Cel), and D-melibiose (Mel), to determine the influence of the glycoside moiety attached to the C 6 or C 4 of glucose (glc) on the chelating and (or) redox reactivity of the saccharide with high oxidation states of chromium.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations